2018
DOI: 10.1111/eff.12393
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale movement ecology of a freshwater top predator, Eurasian perch (Perca fluviatilis), in response to the abiotic environment over the course of a year

Abstract: Fine‐scale underwater telemetry affords an unprecedented opportunity to understand how aquatic animals respond to environmental changes. We investigated the movement patterns of an aquatic top predator, Eurasian perch (Perca fluviatilis), using a three‐dimensional acoustic telemetry system installed in Kleiner Döllnsee (25 ha), a small, shallow, mesotrophic natural lake. Adult piscivorous perch (N = 16) were tagged and tracked in the whole lake at a minimum of 9‐s intervals over the course of one year. Perch i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…Perch are known to be social foragers and group naturally in the wild even when prey fish are abundant and widely distributed (Nakayama et al . ), which we predict fosters individualism bordering territoriality depending on spatial patchiness. Adult northern pike, Esox lucius , in contrast, forage on the same prey species in the same habitats as perch, but showed agonistic reactions and avoidance behaviour and were most successful when foraging alone (Eklöv ), as predicted by our framework.…”
Section: Resultsmentioning
confidence: 69%
“…Perch are known to be social foragers and group naturally in the wild even when prey fish are abundant and widely distributed (Nakayama et al . ), which we predict fosters individualism bordering territoriality depending on spatial patchiness. Adult northern pike, Esox lucius , in contrast, forage on the same prey species in the same habitats as perch, but showed agonistic reactions and avoidance behaviour and were most successful when foraging alone (Eklöv ), as predicted by our framework.…”
Section: Resultsmentioning
confidence: 69%
“…; Nakayama et al . , ; Strople et al . ), and our model can easily accommodate temperature dependencies as well.…”
Section: Main Insights From Our Behavioural‐bioenergetics Model and Pmentioning
confidence: 99%
“…Hydroacoustic surveys in combination with methods such as trawling, seining, or drift‐netting represent suitable gear types for surveying mid‐channel or deep water habitats (Loisl et al, ; Rudstam, Parker‐stetter, Sullivan, & Warner, ). Furthermore, Nakayama et al () showed how fine‐scale underwater telemetry provides a means of studying the response of fish behaviour to changing environmental conditions, not only during diel cycles but also throughout the whole year. Regardless, the majority of studies have shown that boat electrofishing yields a representative sample of riverine fish communities and provides a suitable method to investigate fish‐habitat relationships (Boisclair et al, ; Flotemersch & Blocksom, ; Radinger et al, ).…”
Section: Discussionmentioning
confidence: 99%